2013
DOI: 10.1155/2013/154542
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and Binding Profile of Lectins from the GenusCanavaliaon Brine Shrimp

Abstract: Lectins are sugar-binding proteins widely distributed in nature with many biological functions. Although many lectins have a remarkable biotechnological potential, some of them can be cytotoxic. Thus, the aim of this study was to assess the toxicity of five lectins, purified from seeds of different species of Canavalia genus. In order to determine the toxicity, assays with Artemia nauplii were performed. In addition, a fluorescence assay was carried out to evaluate the binding of lectins to Artemia nauplii. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Heavily glycosylated digestive tract of nauplii might contain α-galactoside sugars that became specifically recognized by MytiLec-1 as addition of 0.1M melibiose [Gal(α1-6)Glc] sugar reduced the binding of FITC-labeled MytiLec-1 (Figure 3C). This finding was in line with the properties of previously reported lectins from the genus Canavalia [23]. Though plant lectins are usually more toxic than animal lectins, this result suggested that animal lectins follow similar mechanisms to interrupt the functions of gut cells of Artemia or to destroy those cells [24,25].…”
Section: Discussionsupporting
confidence: 88%
“…Heavily glycosylated digestive tract of nauplii might contain α-galactoside sugars that became specifically recognized by MytiLec-1 as addition of 0.1M melibiose [Gal(α1-6)Glc] sugar reduced the binding of FITC-labeled MytiLec-1 (Figure 3C). This finding was in line with the properties of previously reported lectins from the genus Canavalia [23]. Though plant lectins are usually more toxic than animal lectins, this result suggested that animal lectins follow similar mechanisms to interrupt the functions of gut cells of Artemia or to destroy those cells [24,25].…”
Section: Discussionsupporting
confidence: 88%
“…The Artemia lethality test has been used successfully to determine the toxicity of bioactive compounds that have a variety of pharmacological activities, including anticancer agents, antivirals, insecticides, pesticides, and anti‐HIV compounds (Carballo et al ., ; Pervin et al ., ; Ho et al ., ). Other studies evaluated the toxic effect of some ConA‐like lectins, and they reported LC 50 values ranging from 45.85 to 376.48 µg/ml (Pinto‐Junior et al ., ; Arruda et al ., ). In comparison with similar lectins, DrfL exhibited low toxicity against Artemia sp.…”
Section: Resultsmentioning
confidence: 97%
“…within 24 and 48 hours. In contrast, Arruda et al [62] showed that several lectins belonging to the Diocleinae subtribe are toxic to Artemia with lethal concentrations as low as 54.48, 110.51, 146.55 μg/mL for ConBr, ConGF, and ConM, respectively. Based on these results, CsL can be considered nontoxic to Artemia sp.…”
Section: Toxicity Of Csl Against Artemia Naupliimentioning
confidence: 93%
“…The lethality test using Artemia is a simple preliminary assay to determine toxicity of CsL against cells [17,62,63,64]. When toxicity of CsL for Artemia was examined using lectin concentrations ranging between 3.125 and 200 μg/mL, it was found that this lectin is innocuous to Artemia sp.…”
Section: Toxicity Of Csl Against Artemia Naupliimentioning
confidence: 99%